AGORAPHOBIA ANALYSIS EXPERIENCED BY THE MAIN CHARACTER IN MARIA SEMPLE’S WHERE’D YOU GO, BERNADETTE NOVEL - Ara Najma Indah; Ely Nurmaily (English Literature Study Program, Faculty of Arts and Education Universitas Teknokrat Indo, 2022)
This research is entitled agoraphobia analysis experienced by the main character in Maria Semple's where'd you go, Bernadette novel. This research aims to discuss the portrayal of Agoraphobia that was experienced by the character Bernadette in Maria Semple’s novel entitled where'd you go, Bernadette. Bernadette is the main character in this novel that is assumed to suffer from agoraphobia due to some things in the past that made her very disappointed and traumatized. Therefore, the objectives of this research are to find out what symptoms are experienced by Bernadette; the writers also describes the agoraphobia seen in the main character in the novel whether she is suffering from agoraphobia or not in the novel Where'd you Go, Bernadette.This research also used a descriptive qualitative method to describe and explain the data. The writers collected the data in the form of dialogues, words, and sentences from the main data resource, which is the novel where'd you go, Bernadette. To support the data, supporting data from articles and journals are also used. This research used psychology literature as the approach. To find the result, the writers used a theory from the American Psychiatric Association (2013) in Barlow, David H (2014), and supported by the theory from American Psychiatric Association (2013); which explains the symptoms of agoraphobia.The theory helps the writers to find the causes and symptoms of Agoraphobia experienced by characters. Where the cause of Agoraphobia she suffers is due to the trauma she went through and bad experiences in her past. The results of this research show that Bernadette in the novel where'd you go, Bernadette suffered from Agoraphobia because she showed the symptoms of Agoraphobia.Keyword: Agoraphobia, Bernadette Fox, symptoms of agoraphobia